Impact of Tobacco Expenditure on Household Spending Patterns in Kenya - Magati, Peter; Mureithi, Leopold; Nyangena, Wilfred (European Scientific Journal, ESJ, 2020)
Despite measures to control tobacco use in Kenya, there is still an increasing importance in the use of tobacco. This is seen by the growth in per capita consumption over time. Tobacco, being an addictive product, creates a situation where consumers allocate part of their resources towards its consumption and therefore positions the use of tobacco as an important expenditure decision in households in Kenya. Due to budget constraints faced by households in Kenya, tobacco consumption may crowd out consumption of essential goods and services. This paper therefore focuses on the impact of tobacco expenditure on household spending patterns in Kenya. Using the 2005/2006 Kenya Integrated Household and Budget survey, a Quadratic Almost Ideal Demand System was used to estimate a system of Engel curves to check whether the differences in expenditure between the two types of households is as a result of tobacco use or not. Results suggest that tobacco crowds out the consumption of food, health care, schooling, clothing, entertainment, house care, and personal care. Geographical location and socio-economic standing of households have a significant influence on the magnitude and pattern of crowding out. The policy implication of this finding is that tobacco control should be an integral part of governments’ poverty alleviation strategy.